الاعتراضات الفرعية في التنفيذ الجبري على العقارات - هيبة قديري, أحلام قديري (Universté ELOUEd-جامعة الوادي, 2019)
نظم المشرع الجزائري وسائل قانونية إجرائية لتصفية كل العوارض التي تعترض إجراءات التنفيذ قبل الوصول الى جلسة البيع وفي مختلف مراحلها و هي تعد منازعات فرعية في التنفيذ الجبري على العقارات، ومن بين هاته الوسائل الاعتراض على قائمة شروط البيع والهدف منها هو تطهير العقار من كل المنازعات التي لا تسمح للتنفيذ الجبري إنتاج آثاره، وقد أوجب المشرع الإلتزام بالإجراءات المحددة قانونا لإبداء الاعتراضات على قائمة شروط البيع، من أجل التمسك بتعديل شروط البيع أو ببطلان إجراءات التنفيذ على العقار بادعاء وجود عيوب متعلقة بشكل الإجراءات أو بالموضوع أو الاعتراض عليها لأي سبب آخر بشرط أن يكون هذا السبب مؤثرا في التنفيذ من ناحية صحته أو عدم صحته، جوازه أو عدم جوازه، ويختلف الاعتراض بحسب موضوعه فقد يكون في بطلان الإجراءات أو ابداء الملاحظات على شروط البيع، أو طلبات خاصة تتعلق بإجراءات التنفيذ ووقف البيع للعقار. وإضافة لذلك منح المشرع الجزائري إمكانية الاعتراض أثناء الجلسة المحددة لبيع العقار المحجوز بالمزاد العلني من خلال الاعتراض على صحة الإعلان وإلغاء إجراءات النشر والتعليق المشوبة بعيوب في الإجراءات، وكرس الاعتراض بوسيلتي طلب التأجيل و/أو وقف البيع لكل ذي مصلحة، وقد خصص المشرع حماية للغير عن طريق دعوى طلب استحقاق العقار بضمان التنفيذ بطريق الحجز على العقار غير مشهر، وهي تعد من الوسائل القانونية للمنازعة في التنفيذ لها أحكاما خاصة ولا يمكن إعتبارها من المنازعات الفرعية في التنفيذ الجبري إلا إذا أثرت في إجراءات البيع وذلك بالحكم بوقفها. The Algerian lawmakers have organized legal and procedural means to filter all the obstacles that the implementation procedures face before reaching the sale session and in its various stages. These are considered subsidiary disputes in the forcible execution of real estate. Among these means is the objection to sale terms in order to purify the property from all disputes that do not allow forcible executions to be in effect. The legislator has required adherence to the legally specified procedures for expressing objections to the sale terms in order to adhere to the amendment of the terms or to invalidate the execution procedures on the property claiming that there are defects related to the form of the procedures or objecting to them for any other reason that affects the execution it terms of validity and permissibility. The objection varies according to its subject, it may be in the procedures’ invalidity, observations on the sale terms, or special requests related to the procedures and sale stopping time. In addition, the Algerian legislator granted the possibility of objecting during the session specified for the sale of the seized property by public auction by objecting to the validity of the advertisement and canceling the publishing and commenting procedures tainted by flaws in the procedures. The objection is by two methods of requesting the postponement and / or stopping the sale to everyone who has an interest. To protect others, the legislator authorized requesting the entitlement of the property with an execution guarantee through seizing the estate that is not declared. That is one of the legal means of dispute with special provisions and cannot be a part of the sub-disputes in the forcible execution unless it affects the sale procedures through ruling to stop it.
مذكرة ماستر
Keywords: العوارض- للتنفيذ الجبري - شروط البيع; implementation-These are considered subsidiary